The Effectiveness of Al-Qawā’id Wa Al-Tarjamah Method on the Ability to Read the Book of Al-Turāts - Shalihah, Siti; Maksum, Ali; Nurvaliza, Nurvaliza; Rossalia, Rossalia; Mohamed, Norahida (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2024)
This study aims to analyze the implementation of the al-qawā’id wa al-tarjamah method at Islamic Boarding School Hidayatul Mubtadi'in and evaluate its effectiveness in improving students' ability to read kitab al-turāts (classical Islamic texts). Employing a descriptive qualitative approach, data were collected through interviews, observations, questionnaires, and supporting documents. The findings reveal that the al-qawā’id wa al-tarjamah method significantly enhances students' reading abilities, as shown by improved post-test scores compared to pre-test scores across all three classes: Class 1 (82:68), Class 2 (84:71), and Class 3 (92:78). Moreover, the post-test scores exceeded the predetermined targets for each class, indicating the method's effectiveness. Observations also highlight high levels of student engagement and motivation, with learners actively participating in activities such as memorization, completing assignments, and murāja'ah (lesson reviews). These findings underscore the method's role in fostering academic achievement and enthusiasm for learning. The study's implications suggest that this method could serve as a model for other Islamic boarding schools aiming to improve students' mastery of classical texts. To enhance its application, integrating modern pedagogical tools such as digital platforms may further optimize learning outcomes. Future research should explore the method's long-term impact, its adaptability in non-boarding school settings, and comparisons with alternative teaching methods to maximize its potential benefits.